Biorenewable resources - Brown, Robert C (Wiley Blackwell, 2014)
Includes bibliographical references and index; Fundamental concepts in engineering thermodynamics -- Organic chemistry -- The biorenewable resource base -- Production of biorenewable resources -- Products from biorenewable resources -- Biochemical processing of carbohydrate-rich biomass -- Thermochemical processing of lignocellulosic biomass -- Processing of oleaginous biomass -- Processing of biorenewable resources into natural fibers -- Environmental impact of the bioeconomy -- Economics of biorenewable resources -- Biorenewable policy.